Оцінка швидкості йонізації Li електронним ударом з використанням немаксвеллівської функції розподілу - Dilmi, S.; Boumali, A. (Publishing house "Academperiodika", 2021)
We report an estimate of the cross-section and rate of electron-impact ionization of Li. The FAC code (Flexible Atomic Code) is used in order to determine the cross-section and to calculate the level of energy. We evaluate the effect of electron energy distribution functions on the measurement of the ionization rate for a non-Maxwellian energy distribution, if the fraction of hot electrons is small. In several types of plasma, it has been observed that certain (hot) electrons are governed by a non-Maxwellian energy distribution. These electrons affect the line spectra and other characteristics of plasma. By using a non-Maxwellian distribution of energies, we revealed the sensitivity of the electron-impact ionization rate of Li to types of the electron energy distribution and to the fraction of hot electrons.